Celebrating 100 years of the Debye scattering equation. Issue 6 (1st November 2016) - Scardi, Paolo; Billinge, Simon J. L.; Neder, Reinhard; Cervellino, Antonio
Abstract : One hundred years of the Debye scattering equation are celebrated with a series of articles arising from the DSE 2015 conference. Abstract : One hundred years of the Debye scattering equation are celebrated with a series of articles arising from the DSE 2015 conference.